The War on Cancer An Anatomy of Failure, A Blueprint for the Future - Faguet, Guy B. (Springer Netherlands : Imprint: Springer, 2005)
After reviewing the history of cancer and its impact on the population, Dr. Faguet exposes the antiquated notions that have driven cancer drug development, documents the stagnation in treatment outcomes despite major advances in cancer genomics and growing NCI budgets, and identifies the multiple factors that sustain the status quo. He shows that, contrary to frequent announcements of breakthroughs, our current cancer control model cannot eradicate most cancers and the reasons why. Significantly, this book also delineates a way forward via a shift from the discredited cell-kill approach of the past to an integrated, evidence-driven cancer control paradigm based on prevention, early diagnosis, and pharmacogenomics. The author's views are based on data published in mainstream scientific journals and other reliable references, 432 of which are cited.